The Arms of Moravia and Silesia - Zdeněk Koudelka (Journal on European History of Law)
Moravia and Silesia are historical lands which nowadays create the eastern part of the Czech Republic. Nevertheless, the major part of Silesia belongs to contemporary Poland, a smaller part belongs to Saxony. Moravia as a margraviate and Silesia as a duchy belonged as integral parts to the Holy Roman Empire and were feudally dependent on the Czech king, later on the Habsburg and Prussian state. Their historical lines projected in that aspect that their coats of arms exist in two versions.